Exercise Motivation Mediates Parenting Effects on Physical Fitness Among Aviation Cadets: A PLS-SEM Study - Nafana Aulia Rochida; Ahmad Mubarok; Miko Andi Wardana; Afen Sena; I Gede Adi Putra Pratama (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
Physical fitness is essential for aviation cadets because operational readiness requires sustained physical and psychological capacity. This study examined whether institutional parenting, exercise motivation, and the educational environment explain physical fitness among cadets at the Indonesian Aviation Academy Banyuwangi. An explanatory quantitative design was applied to 94 respondents using census sampling. Parenting, motivation, and educational environment were measured with five-point Likert instruments, while fitness was represented by objective performance indicators. Data were analyzed using partial least squares structural equation modeling and bootstrapping. The educational environment significantly predicted physical fitness (beta = 0.411, p = .001) and exercise motivation (beta = 0.370, p = .003). Exercise motivation predicted physical fitness (beta = 0.353, p = .004), while institutional parenting strongly predicted motivation (beta = 0.501, p < .001) but had no significant direct effect on fitness (beta = 0.193, p = .051). The indirect parenting-motivation-fitness effect was significant (beta = 0.177, p = .013). The model explained 75.0% of fitness variance. The findings indicate that supportive but structured parenting is most effective when it builds internal motivation, while a conducive educational environment provides the context needed to sustain cadets' fitness.